Stochastic Income Statement Planning and Emissions Trading - Henry Dannenberg; Wilfried Ehrenfeld (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
Since the introduction of the European CO2 emissions trading system (EU ETS), the development of CO2 allowance prices is a new risk factor for enterprises taking part in this system. In this paper, we analyze how risk emerging from emissions trading can be considered in the stochastic profit and loss planning of corporations. Therefore we explore which planned figures are affected by emissions trading. Moreover, we show a way to model these positions in a planned profit and loss account accounting for uncertainties and dependencies. Consequently, this model provides a basis for risk assessment and investment decisions in the uncertain environment of CO2 emissions trading. – – Dieses Papier behandelt die Frage, wie durch den CO2-Zertifikatehandel verursachte Risiken in der stochastischen Gewinn-und Verlustplanung von Unternehmen Berücksichtigung finden können. Es wird zunächst diskutiert, welche Plangrößen durch den Zertifikatehandel betroffen sind. In einem weiteren Schritt werden Möglichkeiten aufgezeigt, wie diese Positionen unter Einbeziehung von Unsicherheiten sowie Abhängigkeiten in einer Plan-Gewinn-und Verlustrechnung modelliert werden können. Das vorgestellte Modell stellt eine Basis für Risikobewertungen und Investitionsentscheidungen im unsicheren Umfeld des CO2-Zertifikatehandels dar.
urn:nbn:de:101:1-2010031959
Keywords: D81; G32; L59; Q54; Q56; Q58; 330; CO2; emissions trading; EU ETS; risk; stochastic business planning; CO2; Emissionshandel; EU ETS; Risiko; stochastische Unternehmensplanung; Emissionshandel; Gewinn- und Verlustrechnung; Unternehmensplanung; Risikomanagement; Stochastischer Prozess; Theorie